1998
DOI: 10.1042/bj3340519
|View full text |Cite
|
Sign up to set email alerts
|

Restricting mobility of Gsα relative to the β2-adrenoceptor enhances adenylate cyclase activity by reducing Gsα GTPase activity

Abstract: The beta2-adrenoceptor (beta2AR) activates the G-protein Gsalpha to stimulate adenylate cyclase (AC). Fusion of the beta2AR C-terminus to the N-terminus of Gsalpha (producing beta2ARGsalpha) markedly increases the efficiency of receptor/G-protein coupling compared with the non-fused state. This increase in coupling efficiency can be attributed to the physical proximity of receptor and G-protein. To determine the optimal length for the tether between receptor and G-protein we constructed fusion proteins from wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…the "spacer peptide" between the receptor and the G protein, could theoretically impair the ability of the G-protein to interact correctly with the receptor by inducing conformational constraint; however, it has previously been demonstrated that truncation of the receptor tail of the ␤ 2 -adrenergic receptor is well tolerated in G-protein fusions (21). The backbone of the remaining C terminus in the presently employed ⌬-tail constructs can in fact still in an extended form stretch ϳ86 Å away from the receptor, which should ensure a reasonable degree of conformational freedom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the "spacer peptide" between the receptor and the G protein, could theoretically impair the ability of the G-protein to interact correctly with the receptor by inducing conformational constraint; however, it has previously been demonstrated that truncation of the receptor tail of the ␤ 2 -adrenergic receptor is well tolerated in G-protein fusions (21). The backbone of the remaining C terminus in the presently employed ⌬-tail constructs can in fact still in an extended form stretch ϳ86 Å away from the receptor, which should ensure a reasonable degree of conformational freedom.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in the ⌬-tail constructs, we do observe a tendency toward a lower coupling efficacy as compared with the wildtype receptor, both in cAMP and in inositol phosphate turnover. This could possibly be ascribed to an impaired interaction between either the receptor and the G-protein or between the G-protein and the effector molecule (adenylylcyclase and phospholipase C ␤) (21).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence suggesting that both kinds of modification can target their cognate protein (GAP43, G i/o subunit, Lyn) to such membrane specializations (20,(43)(44)(45)(46). Theoretically, it should be possible to design tethering signals that do not target the G-protein to rafts and thus examine the consequences for signaling (47). Indeed, recently differential trafficking to membrane domains has been observed for a variety lipid modifications attached to fluorescent proteins (48).…”
Section: Fluorescent G-proteinsmentioning
confidence: 99%
“…Following that observation, similar constructs were created for a variety of studies, as extensively reviewed in Refs. 2-4. Often the 1:1 stoichiometry, presumably imposed by fission, was reported to facilitate the study of GPCR-mediated activation of ␣-subunits in transfected cells (5)(6)(7)(8)(9)(10)(11)(12), or it was exploited to test the specificity of signals generated by GPCR and multiple ␣-subunits (13)(14)(15)(16)(17)(18)(19)(20). However, the interpretation of experiments in which fusion proteins are used as investigational probes requires an understanding of how receptor and G proteins interact in such chimeric proteins.…”
mentioning
confidence: 99%